Faktor Pengaruh Minat Pengguna Financial Technology pada E-Wallet (Survei pada Pengguna Shopeepay) - Aisyani Redita Nur Yuliati; Juniati Gunawan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to examine the factors that influence individual interest in the use of financial technology. This study uses the Theory of Planned Behavior (TPB) by examining several factors according to the theory taken. In this study, only 6 interest factors were filtered from several studies, the reason being that it refers to previous research which generally uses the Theory of Planned Behavior (TPB). Research data obtained from the results of online questionnaire collection. The sampling technique used probably sampling method with simple random sampling technique with a total sample of 148 people. The results of this study indicate that the variables of user convenience, social influence, security, usability, trust and promotion are proven to affect individual interest in the use of financial technology. Hypothesis testing in this study uses a structural model (Inner Model) with the SmartPLS application